Mitigating Learning Apathy: Study of Problems in Civics Learning - Amrulloh, Miftah; Patmisari, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to determine the role of PPKn teachers in overcoming students' learning apathy at SMP Muhammdiyah 7 Surakarta. This study was carried out for approximately one month using descriptive qualitative study methods using facts in the field to provide a clearer picture. The data and data sources for this research are the results of interviews with PPKn teachers, students, and school principals, as well as the results of observations carried out by researchers at schools. This study uses observation instruments and interview instruments. The data collection techniques used in this research are observation, interviews, and documentation. The results of this study show that civic teachers have an essential role in overcoming students' learning apathy. The role of the PPKn teacher at SMP Muhammadiyah 7 Surakarta is as follows: First when students are not involved in the learning process, the teacher plays a vital role in overcoming this problem by looking for or calling them to be informed about the material explained in class and given sanctions. Second, when students ignore the teacher when the teacher explains the lesson material, the teacher's role in overcoming this problem is to develop a learning model that does not only use the lecture method. Third, when students do not dare to ask questions to the teacher, the teacher's role in overcoming this problem is to understand because each student has different abilities. Fourth, when students do not answer questions asked by the teacher or other students, what the teacher does is give additional points to raise student motivation. Fifth, when students do not dare to respond to answers from other students, the teacher's role is to motivate students why they do not answer questions and so on. Sixth, when students do not provide conclusions at the end of the lesson, the teacher explains that only students who pay attention during learning can conclude the material. Sixth, when students do not do the assignments given by the teacher, in this case, the teacher has a vital role in preventing this by providing sanctions in the form of doubling the assignment.